PRODUCTION OF WOOD CHARCOAL AS BIO-REDUCTOR IN BLAST FURNACE - Isnugroho, Kusno; candra, david (Teknologi Indonesia, 2015)
A study on bio-reducer using lamtoro and rubber wood raw materials had been conducted. This study used carbonizing furnace made from mild-steel which was equipped with absorber to reduce emitting exhaust gas during process. The absorber used came from activated zeolite inserted with TiO2. Carbonizing process was conducted in 700C, 800C, and 900C temperatures. The produced results, both from lamtoro and rubber wood raw materials, underwent reduction along with increasing carbonizing temperatures. Yields from rubber wood at 700C, 800C, and 900C were 23.12%, 21.32%, 20.26%, respectively, and yields from lamtoro wood at 700C, 800C, and 900C were 26.51%, 25.13%, and 24.12%, respectively. Ultimate and proximate test using ASTM D.3174, ASTM D.3173, ASTM D.3175, ASTM D.5373 and ASTM D.4239 showed that bio-reducer product in form of charcoal made from lamtoro and rubber wood had fulfilled specifications as a reducer in iron ore processing. Test result of emitting exhaust gas showed reduced CO and NOx gases during carbonizing process.